Initial study on the impact of thermal history on building occupants’ thermal assessments in actual air-conditioned office buildings - Fadeyi, Moshood Olawale (2014)
This preliminary study examines the influence of longer thermal history on building occupants' thermal sensation, perceived air temperature and thermal acceptability during the initial period of occupancy and after an extended period of occupancy in actual air-conditioned office buildings. Each of the subjects' forty-eight-hour thermal history was assessed using measured air temperatures with a wireless chip, “iButton,” placed close to their skins. Subjects did thermal assessments of their offices through a web-based survey link while they had their “iButton” on them. In addition, the subjects were required to fill the survey 4 times in their offices: during initial occupancy, before lunch break, after lunch break and before they left their offices for the day. Subjects' thermal assessments followed typical transient perceptions during initial occupancy of their offices. However, subjects' thermal assessments followed typical steady-state perceptions after extended period of occupancy because of diminished influence of thermal history. Maximum thermal acceptability occurred around neutral point of rating scales of thermal sensation and perceived air temperature throughout occupancy periods. Additionally, gender and body mass index influenced building occupants' thermal assessments. These results provide understanding on how thermal history influences occupants' thermal sensation, perceived air temperature, and thermal acceptability should be accounted for in the design and operation of air-conditioned buildings where occupants spend considerable amount of time.